2000
DOI: 10.1046/j.1365-3113.2000.00104.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological variation and mating compatibility within the mealybugs Pseudococcus calceolariae and P. similans (Hemiptera: Pseudococcidae), and a new synonymy

Abstract: Summary A laboratory study of isolines of Pseudococcus calceolariae (Maskell) and P. similans (Lidgett) collected from Hawke's Bay and Auckland, two widely separated regions in the North Island of New Zealand, threw doubt on the validity of the defining characters of these species. For P. similans, the number and position of oral rim tubular ducts varied widely and sometimes fell outside the defined limits for the species, and characteristic ‘stout abdominal setae’ were lost in the F1 generation. The morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 9 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…The morphological analysis revealed that the phenotype of P. calceolariae used in this study corresponds to the most common one present in Australia and new Zealand, as the four parameters measured were well within the range reported for this phenotype (Cox, 1987;Williams, 1985), and were different from the phenotype described originally as P. similans and later synonymized with P. calceolariae (Charles et al, 2000) (Table 1).…”
Section: Identification Of Species and Phenotypesupporting
confidence: 64%
See 1 more Smart Citation
“…The morphological analysis revealed that the phenotype of P. calceolariae used in this study corresponds to the most common one present in Australia and new Zealand, as the four parameters measured were well within the range reported for this phenotype (Cox, 1987;Williams, 1985), and were different from the phenotype described originally as P. similans and later synonymized with P. calceolariae (Charles et al, 2000) (Table 1).…”
Section: Identification Of Species and Phenotypesupporting
confidence: 64%
“…For identification of the phenotype, the following characters were determined according to Charles et al (2000): length of tibia plus tarsus of hindlegs, combined length of trochanter and femur of hindlegs, ratio hind tibia:tarsus and number of oral rim tubular ducts. Distances were measured by calibrating digital photographs taken at a magnification of 20x (Micropublisher 3.3 RTV, Qimaging, Burnaby, BC, Canada) with a known standard (100 um = 252 pixels), using the software Image J 1.40 (http://rsb.info.nih.…”
Section: Identification Of Species and Phenotypementioning
confidence: 99%
“…Among the scale insects (Coccoidea), laboratory-induced inter-species hybrids have been observed in the mealybug family (Pseudococcidae) [19], [20], [21], [22], [48].…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to generate phylogenetic hypotheses for the family are confounded by a paucity of useful morphological characters in adult females as a result of reduction (Ferris, 1950; Cox, 1987), substantial intraspecific polymorphism in some species (Danzig, 1980; Cox, 1987), and environmental influences on morphology affecting character states of the wax ducts and pores (Cox, 1983; Charles et al ., 2000), as well as other features deemed useful in identification. Also, significant electrophoretic differences have been detected among collections of mealybugs which were considered to be one species based on morphology (Nur, 1977).…”
Section: Introductionmentioning
confidence: 99%